Cellular and molecular biology of filamentous fungi - Borkovich, Katherine A.; Ebbole, Daniel J. (Monograph, ASM Press., 2010)
"Incorporating the latest findings from such disciplines as physiology, taxonomy, genomics, molecular biology and cell biology, this publication is an ideal starting point for any research study of filamentous fungi."--Pub. desc